Nagios 3 enterprise network monitoring including plug-ins and hardware devices - Schubert, Max. (Burlington, MA : Syngress Pub., 2008)
Nagios is an Open Source network, hardware, and application monitoring program. It is designed to inform system administrators of problems on their networks before their clients, end-users or managers do. Nagios is a SysAdmin's best friend. Nagios is installed on over 300,000 machines worldwide, and truly is a global product: approximately 25.6% of users are in the U.S., and 30% in EMEA. Nagios can monitor everything from network bandwidth to the temperature and humidity in a server room. SysAdmins are able to use Nagios for such a variety of purposes through custom software "plug ins" and third party hardware. SysAdmins customize these plug ins instructing Nagios to monitor the servers, applications, or devices that are most critical to their network infrastructure. These plug ins also allow SysAdmins to integrate Nagios with other monitoring devices and applications like Snort and Wireshark. Nagios can also be fully integrated with third party environmental monitoring devices and remote power supplies. When Nagios detects a problem, it can notify the SysAdmin in a variety of different ways (email, instant message, SMS, etc.). Current status information, historical logs, and reports can all be accessed via a web browser. Nagios could send a text message to a SysAdmin sitting on his couch at home that the temperature in the server room is too hot and could potentially damage the equipment. The SysAdmin can then check the status of the server from home using his Nagios Web interface, and then coordinate with the appropriate facility management personnel to check the air conditioning in the server room. This is merely one example of Nagios? capabilities. The same scenario could be applied to an overloaded Exchange server, a router being pounded by a Denial of Service Attack, or a user accessing or downloading unauthorized materials. * Contains complete case study on deploying Nagios in an enterprise environment * Companion website offers a wide variety of working Scripts for customizing Nagios plug-ins * Helps organizations adhere to federally mandated compliance regulations such as Sarbanes- Oxley or HIPAA * Details how to integrate Nagios with third-party hardware.
Foreward; Introduction; Chapter 1: Nagios 3; Chapter 2: Designing Configurations for Large Organizations; Chapter 3: Scaling Nagios; Chapter 4: Plugins, Plugins, and More Plugins; Chapter 5: Add-ons and Enhancements; Chapter 6: Enterprise Integration; Chapter 7: Intrusion Detection and Security Analysis; Chapter 8: Case Study: Acme Enterprises.
Includes index.
Keywords: Computer networks -- Monitoring; Computer networks -- Management -- Automation; Electronic books